In vivo pectin solubility in ripening and chill-injured tomato fruit - Almeida, Domingos P. F. (2010)
In vivo pectin solubility was examined in ripening and chill-injured tomato fruit with down-regulated polygalacturonase (PG, EC 3.2.1.15) activity and untransformed wild-type fruit by analyzing a pressure-extracted fluid of apoplastic origin. Pectin concentration in the apoplastic fluid increased threefold during ripening and was not affected by endogenous PG. In contrast, PG strongly affected pectin concentration in a bulk pericarp fluid obtained after tissue disruption. There was a 14-fold increase in bulk pectin levels during ripening of PG-antisense fruit and a 36-fold increase in wild-type. Pectins soluble in the apoplastic fluid decreased slightly during storage of fruit at 5ºC for 14 days but increased considerably upon subsequent transfer to 15ºC. Concentration of monomeric galactose in the apoplastic fluid increased during ripening from 41 to 67 µg mL⁻¹. Galactose levels were threefold to fourfold higher in the bulk than in the apoplastic fluid. Low-temperature storage caused a 50% reduction in the galactose present in the bulk fluid and a 20% reduction in apoplastic concentration of galactose. These results indicate that pectin dissolution in ripening tomato fruit is PG-independent even though the enzyme is catalytically active in ripe fruit. Low-temperature storage reduces in vivo pectin solubility, an effect that is reversed upon transfer to higher temperature following cold storage